(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article deals with such philological sciences as linguistics, applied linguistics, stylistics, speech culture and literary editing. Their interrelationships with each other in the compilation of various text outputs are discussed.